Comparison of PBDE congeners as inducers of oxidative stress in zebrafish. (7th April 2015) - Usenko, Crystal Y.; Abel, Erika L.; Kudela, Molly; Janise, Annie; Bruce, Erica D.
Abstract: A proposed primary pathway through which polybrominated diphenyl ethers (PBDEs) disrupt normal biological functions is oxidative stress. In the present study, 4 PBDE congeners were evaluated for their potential to initiate oxidative stress in zebrafish during development: BDE 28, BDE 47, BDE 99, and BDE 100. N‐ acetylcysteine (NAC) was used to increase intracellular glutathione concentrations and only decreased the effects of BDE 28 at 10 ppm and 20 ppm and BDE 47 at 20 ppm. N‐ acetylcysteine coexposure did not alter the rates of mortality or curved body axis compared with PBDE exposure alone. The activity of glutathione‐ S ‐transferase (GST) was not altered at 24 h postfertilization (hpf), but increased following 10 ppm BDE 28 exposure at 120 hpf. Transcription of several genes associated with stress was also evaluated. At 24 hpf, cytochrome c oxidase subunit 6a (COX6a) transcription was up‐regulated in embryos exposed to BDE 99, and BDE 28 exposure up‐regulated the transcription of Glutathione‐ S‐ transferase‐pi (GSTpi). At 24 hpf, glutamate‐cysteine ligase (GCLC) was slightly down‐regulated by all congeners evaluated. At 120 hpf, TNF receptor‐associated protein 1 (TRAP1) and COX6A were up‐regulated by all congeners, however GSTpi was down‐regulated by all congeners. The results of quantitative real‐time transcription polymerase chain reaction are mixed and do not strongly support a transcriptional response to oxidative stress. According to the authors' data, PBDEs do not induce oxidative stress. Oxidative stress may occur at high exposure concentrations; however, this does not appear to be a primary mechanism of action for the PBDE congeners tested. Environ Toxicol Chem 2015;34:1154–1160. © 2015 SETAC